Impact of ethanol extract of Anamirta cocculus (Linn.) seeds on tissue damage biomarkers of the predatory catfish Heteropneustes fossilis (Bloch.). Issue 4 (4th July 2018) - Dar, Umer Qadir; Paul, V. I.
ABSTRACT: Seeds of the phytopiscicide Anamirta cocculus are used recently to eradicate unwanted fishes from aquaculture ponds during pond preparation. However, the mode of action of A. cocculus and the biochemical responses caused to exposed fishes largely remain unexplained. The present study attempts to assess the impact of 24 h LC50 (18.79 ppm) of the ethanolic extract of A. Cocculus seeds on the tissue damage biomarkers viz., alkaline phosphatase (ALP), acid phosphatase (ACP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) of the predatory wild fish Heteropneustes fossilis . The tissues assayed were brain, gills, liver, kidney, muscle, accessory respiratory organs (ARO) and blood. The exposure has caused varying levels of significant reductions in the activities of all these enzymes in various tissues except blood. The activities of serum phosphatases and aminotransferases became significantly higher in the later stages of exposure. The observations clearly indicate the tissue-damaging effects of A. cocculus seed extract.